2015
DOI: 10.3126/njb.v3i1.14232
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of multidrug resistant bacteria in causing community acquired urinary tract infection among the patients attending outpatient department of Seti Zonal Hospital, Dhangadi, Nepal

Abstract: Involvement of multidrug resistant bacteria in causing community acquired infection is very serious public health issue. The main objective of our study was to determine the prevalence of multidrug resistant bacteria in causing community acquired urinary tract infection. In this study we cultured the 384 mid stream urine samples collected aseptically from the patients attending outpatient department of Seti zonal hospital and having no past history of hospitalization. The organisms isolated were identified by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
25
5
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 9 publications
6
25
5
3
Order By: Relevance
“…Antimicrobial resistance has become a serious global public health issue. Infections caused by drug resistant bacteria are responsible for increased morbidity and mortality [ 25 ]. The selection of the antibiotics for treatment of the bacterial infections should be based on culture and sensitivity reports.…”
Section: Discussionmentioning
confidence: 99%
“…Antimicrobial resistance has become a serious global public health issue. Infections caused by drug resistant bacteria are responsible for increased morbidity and mortality [ 25 ]. The selection of the antibiotics for treatment of the bacterial infections should be based on culture and sensitivity reports.…”
Section: Discussionmentioning
confidence: 99%
“…The bacterial isolates showing resistance toward three or more different classes of antibiotics were reported as multidrug resistant (MDR) [9].…”
Section: Performance Of Antimicrobial Susceptibility Testingmentioning
confidence: 99%
“…But recently, drug resistance among the bacteria is present as more serious public health problem. The irrational uses of the antibiotics have driven the evolution of antibiotic resistance, leading to increased morbidity and mortality along with increased health care cost and longer period of hospitalization [8,9]. In terms of the β-lactam antibiotics, bacteria are mainly resistant by producing enzymes, such as extended spectrum beta lactamase (ESBL), AmpC-beta-lactamase and carbapenem hydrolyzing enzymes (carbapenemases) [10].…”
Section: Introductionmentioning
confidence: 99%
“…In the treatment of these UTI patients, gentamicin and ceftriaxone was found effective in more than half of the cases nitrofurantoin in 46% cases, Cotrimoxazole (33%), ofloxacin (30%), nalidixic acid (16%), and ampicillin in only 5% cases. 16 In a meta-analysis, Tenney J, et al reported that 16/20 studies pointed out that the major risk factor leading to MDR microbes in urinary tract is antibiotic abuse and age; other factors includes urinary catheterization, and history of hospital stay and UTI. 17 McAllister R, et al studied UTI cases reported in the residents of nursing homes.…”
Section: 4mentioning
confidence: 99%